2019
DOI: 10.1055/a-0828-7630
|View full text |Cite
|
Sign up to set email alerts
|

Lumen apposing metal stents are superior to plastic stents in pancreatic walled-off necrosis: a large international multicenter study

Abstract: Background and study aims The use of lumen apposing metal stents (LAMS) during EUS-guided transmural drainage (EUS-TD) of pancreatic walled-off necrosis (WON) has gained popularity. Data supporting their use in WON over plastic stents (PS), however, remain scarce. The aim of this study was to compare the clinical efficacy of LAMS (Axios, Boston Scientific) with PS in WON. Patients and methods This was a multicenter, retrospective study involving 14 centers. Consecutive patients who underwent EUS-TD o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(94 citation statements)
references
References 37 publications
5
88
0
1
Order By: Relevance
“…Clinical success was defined as symptom resolution and WON resolution (<3 cm diameter), without mortality or adverse events requiring surgery, without the recurrence of fluid collection or symptoms during follow-up [12]. Need for surgery was defined as surgical intervention (minimally invasive or open) for management of unresolved WON or related complications (multisystem organ failure [MSOF], stent dislodgement with symptomatic pneumoperitoneum, untreatable infection, or intraabdominal bleeding).…”
Section: Methodsmentioning
confidence: 99%
“…Clinical success was defined as symptom resolution and WON resolution (<3 cm diameter), without mortality or adverse events requiring surgery, without the recurrence of fluid collection or symptoms during follow-up [12]. Need for surgery was defined as surgical intervention (minimally invasive or open) for management of unresolved WON or related complications (multisystem organ failure [MSOF], stent dislodgement with symptomatic pneumoperitoneum, untreatable infection, or intraabdominal bleeding).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the rate of early adverse events (AEs) was significantly lower in the FCSEMS group than the DP and LAMS groups; and the rate of delayed AEs was significantly lower in the LAMS group than the DP and FCSEMS groups. Chen et al 12 similarly found that groups in which plastic stents and LAMSs were used for treating WON showed no difference in the AEs rate, but the clinical success rate was significantly higher in the group in which LAMSs were used. In addition, Yang et al 13 evaluated delayed AEs when drainage using LAMSs was performed with WON and PPCs and found that stent occlusion in 18 (29.5%) and 10 (17.5%) patients, respectively, with no cases of delayed bleeding or buried stent being found by followup endoscopy.…”
Section: Endoscopic Therapy For Pancreatic Pseudocyst/walled-off Necrmentioning
confidence: 98%
“…Furthermore, the rate of early adverse events (AEs) was significantly lower in the FCSEMS group than the DP and LAMS groups; and the rate of delayed AEs was significantly lower in the LAMS group than the DP and FCSEMS groups. Chen et al . similarly found that groups in which plastic stents and LAMSs were used for treating WON showed no difference in the AEs rate, but the clinical success rate was significantly higher in the group in which LAMSs were used.…”
Section: Endoscopic Therapy For Pancreatic Pseudocyst/walled‐off Necrmentioning
confidence: 99%
“…In a large, multicenter study including 189 patients with WON, the use of LCMS was associated with higher clinical success (80.4 vs. 57.5%), shorter procedure time, lower need for surgery (5.1 vs. 16.1%), and lower rate of recurrence as compared to plastic stents [31]. However, the superiority of LCMS is not uniform across the published studies.…”
Section: Endoscopic Transmural Drainage: Choice Of Stentsmentioning
confidence: 99%